Value at Risk (VaR) - Gaytán Cortés, Juan (Mercados y Negocios, 2022)
The technique (VaR) is a statistical measure of the risk. It is associated with financial risks related to the high volatility in prices, interest rates, or exchange rates. It is used massively by entities because of the necessity to measure risk in constantly traded portfolios.